2020
DOI: 10.1088/1748-9326/ab875f
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more effective hurricane hazard communication

Abstract: Tropical cyclones are among the most devastating natural disasters that pose risk to people and assets all around the globe. The Saffir-Simpson scale is commonly used to inform threatened communities about the severity of hazard, but lacks consideration of other potential drivers of a hazardous situation (e.g. terrestrial and coastal flooding). Here, we propose an alternative approach that accounts for multiple components and their likelihood of coincidence for appropriate characterization of hurricane hazard.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 39 publications
(35 reference statements)
0
23
0
Order By: Relevance
“…Although numerous studies have estimated different aspects of vulnerability to more visually damaging hazards in the U.S., such as tornadoes [10][11][12], hurricanes [13,14], and floods [15][16][17][18][19], there is not yet any comprehensive assessment of drought vulnerability in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have estimated different aspects of vulnerability to more visually damaging hazards in the U.S., such as tornadoes [10][11][12], hurricanes [13,14], and floods [15][16][17][18][19], there is not yet any comprehensive assessment of drought vulnerability in the U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, Song et al. (2020) identified that rainfall is not always proportional to the wind scale of the TC and therefore, in some cases TS events may accompany more rainfall relative to TC. Moreover, a plethora of studies have looked into TC weakening the drought intensity while drought worsened despite the presence of TC has received less attention.…”
Section: Introductionmentioning
confidence: 97%
“…While the Saffir-Simpson category scale is routinely used to communicate to the public the imminent danger posed by tropical cyclones, more comprehensive alternative scales have been proposed but not widely adopted [26][27][28]. While interpreted by the impact of selected damage types, the Saffir-Simpson scale is actually defined by 1 min average peak near surface wind exceedances over fixed thresholds.…”
Section: Introductionmentioning
confidence: 99%